A novel linker-immunodominant site (LIS) vaccine targeting the SARS-CoV-2 spike protein protects against severe COVID-19 in Syrian hamsters. Issue 1 (1st January 2021) - Zhang, Bao-Zhong; Wang, Xiaolei; Yuan, Shuofeng; Li, Wenjun; Dou, Ying; Poon, Vincent Kwok-Man; Chan, Chris Chung-Sing; Cai, Jian-Piao; Chik, Kenn KaHeng; Tang, Kaiming; Chan, Chris Chun-Yiu; Hu, Ye-Fan; et al.
ABSTRACT: The Coronavirus Disease 2019 (COVID-19) pandemic is unlikely to abate until sufficient herd immunity is built up by either natural infection or vaccination. We previously identified ten linear immunodominant sites on the SARS-CoV-2 spike protein of which four are located within the RBD. Therefore, we designed two linkerimmunodominant site (LIS) vaccine candidates which are composed of four immunodominant sites within the RBD (RBD-ID) or all the 10 immunodominant sites within the whole spike (S-ID). They were administered by subcutaneous injection and were tested for immunogenicity and in vivo protective efficacy in a hamster model for COVID-19. We showed that the S-ID vaccine induced significantly better neutralizing antibody response than RBD-ID and alum control. As expected, hamsters vaccinated by S-ID had significantly less body weight loss, lung viral load, and histopathological changes of pneumonia. The S-ID has the potential to be an effective vaccine for protection against COVID-19.